2011
DOI: 10.1002/gps.2660
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver support groups in patients with dementia: a meta‐analysis

Abstract: Support groups benefit caregivers and findings of this meta-analysis serve as immediate guidance for group facilitators. Future research should include additional outcome variables with our defined factors on effectiveness collected as demographic characteristic data for comparison. A more comprehensive understanding of the effectiveness of support groups is indicated to enhance outcomes for caregivers and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
2
14

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(195 citation statements)
references
References 47 publications
7
165
2
14
Order By: Relevance
“…Supporting group is significantly deliver positive effect to caregiver's psychological health, depression, burden and social relationship 11 .In line with other research which explained that caregiver burden getting decline on intervention group, seen as previous mean was 42 become 35.44, after undergoing education program on 1 month, while on control group was increased, and found significant difference between intervention and control group 12 . This study also shows significant decrease of burden between before intervention measurement and 3 months after undergoing intervention measurement compared to between 3 months after intervention and 6 months after intervention measurement.…”
Section: IVsupporting
confidence: 83%
“…Supporting group is significantly deliver positive effect to caregiver's psychological health, depression, burden and social relationship 11 .In line with other research which explained that caregiver burden getting decline on intervention group, seen as previous mean was 42 become 35.44, after undergoing education program on 1 month, while on control group was increased, and found significant difference between intervention and control group 12 . This study also shows significant decrease of burden between before intervention measurement and 3 months after undergoing intervention measurement compared to between 3 months after intervention and 6 months after intervention measurement.…”
Section: IVsupporting
confidence: 83%
“…Nature of the interventions Four reviews, all rated as moderate quality, reported on information and support interventions (Chien et al, 2011;Parker et al, 2008;Pinquart and Sorensen, 2006;Thompson et al, 2007). Three reviews (Chien et al, 2011;Parker et al, 2008;Pinquart and Sorensen, 2006) examined support only interventions.…”
Section: Information and Supportmentioning
confidence: 99%
“…Three reviews (Chien et al, 2011;Parker et al, 2008;Pinquart and Sorensen, 2006) examined support only interventions. The definition of support groups used by Chien et al (2011) included mutual support groups, educational psychology groups and educational training groups but excluded groups organised on the internet, by telephone or in the community. Parker et al (2008) defined support interventions as those that provide support for problems that inhibit caregiving and provide opportunities for sharing personal feelings and overcome social isolation.…”
Section: Information and Supportmentioning
confidence: 99%
“…Home based interventions, in the form of nurse led case management and community based occupational therapy have been shown to be beneficial with respect to improving caregiver well being, and reducing caregiver burden and ratings of behavioural problems in the person with dementia. [156][157][158][159] Several meta-analyses and systematic reviews [160][161][162][163][164][165] have also found that caregiver interventions improve caregivers' mental health and well-being, reduce caregiver burden and delay institutionalization for the person with dementia. Specifically, support groups as well as psychoeducational interventions help to alleviate depression and improve psychological well being.…”
Section: Caregiver Interventionsmentioning
confidence: 99%